Indigenous Participation in Information Technology Project: Achievements and Challenges of the First Three Years - Evelyn Dyson, Laurel; Robertson, Toni (The Australian Journal of Indigenous Education, 2006)
Abstract In 2002 the Faculty of Information Technology at the University of Technology Sydney began a major initiative to improve the participation of Indigenous Australians in the Information Technology (IT) sector. This followed an initial study which showed that very few Indigenous students undertook studies in IT at university and therefore few found employment as IT professionals. As a result of the new programme, the Faculty’s first Indigenous staff were hired, an Indigenous resource centre was established and the first postgraduate students recruited. In addition, an IT tertiary preparation short course, the Indigenous Pre-IT Program, was launched successfully, the Faculty’s first Indigenous-specific course. With the project, Indigenous student enrolments have increased, mainly as part of the Pre-IT Program and as a result of recruitment of undergraduates from amongst successful Pre-IT Program students. However, retention of undergraduates recruited via special admission provisions has proved difficult despite attempts to secure scholarships and to provide academic support. This paper traces the development of the project and analyses the achievements and challenges in the first three years.